A multiscale tiered approach to quantify contributions: A case study of PM2.5 in South Korea during 2010-2017 - Bae, Minah; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Atmosphere, 2020)
We estimated long-term foreign contributions to the particulate matter of 2.5 μm or less in diameter (PM2.5) concentrations in South Korea with a set of air quality simulations. TheWeather Research and Forecasting (WRF)-Sparse Matrix Operator Kernel Emissions (SMOKE)-Community Multiscale Air Quality (CMAQ) modeling system was used to simulate the base and sensitivity case after a 50% reduction of foreign emissions. The effects of horizontal modeling grid resolutions (27-and 9-km) was also investigated. For this study, we chose PM2.5 in South Korea during 2010-2017 for the case study and emissions from China as a representative foreign source. The 9-km simulation results show that the 8-year average contribution of the Chinese emissions in 17 provinces ranged from 40-65%, which is ~4% lower than that from the 27-km simulation for the high-tier government segments (particularly prominent in coastal areas). However, for the same comparison for low-tier government segments (i.e., 250 prefectures), the 9-km simulation presented lowered the foreign contribution by up to 10% compared to that from the 27-km simulation. Based on our study results, we recommend using high-resolution modeling results for regional contribution analyses to develop an air quality action plan as the receptor coverage decreases.
Keywords: Horizontal grid; Long range transport; PM2.5; Receptor coverage; Source-receptor relationships; Long-range transport; Model horizontal grid resolution; PM2.5; Receptor coverage; Source-receptor relationship